Fixation disparity during reading: Fusion, not suppression - Simon P. Liversedge (Bern Open Publishing, 2008)
In this paper I present a brief review of some recent studies my colleagues and I have carried out to investigate binocular coordination during reading. These studies demonstrate that the eyes are often not perfectly aligned during reading, with fixation disparities of approximately one character on average. Both crossed and uncrossed disparities are common and vergence movements during fixations serve to reduce, but not eliminate disparity. Fixation disparity results in different retinal inputs from each eye, yet a single non diplopic visual representation of the text is perceived when we read. A further experiment, with dichoptically presented target words in normally presented sentence frames, showed that a mechanism of fusion rather than suppression operates at an early stage during visual processing. Saccade metrics appear to be computed according to a unified visual representation based on input from both eyes. based on input from both eyes.